Cognitive impairment in patients with multiple sclerosis - Custodio, Nilton (2018)
Multiple sclerosis is an inflammatory, autoimmune and neurodegenerative central nervous system disease characterized by motor and sensitive function loss; it is considered to be one of the principal causes of disability in young adults. Recently, cognitive impairment has gain considerable attention because it is a frequent symptom that causes disability. Cognitive impairment it is present in 40 to 65% of patients and affects speed of information processing, complex attention, working memory, visual and verbal memory, verbal fluency and executive functions. It may be present in radiologically isolated syndrome, clinically isolated syndrome and in the different stages of the disease; it is responsible for patient’s dependence and for the difficulties to maintain or get an employment. Cognitive impairment is associated to thalamic atrophy and a correlation with brain atrophy and cerebral lesional volume has been observed. Different evaluation tools are available, there are 5 minutes short screening tests and comprehensive 90 minutes batteries. Regarding cognitive impairment treatment, there is not a specific pharmacological treatment, nevertheless, disease modifying therapies could have a favorable influence on cognitive function because of their effects in the reduction of inflammatory activity and brain atrophy. There are no conclusive data about the efficacy of cognitive stimulation because of the diverse techniques employed and the different measures used to evaluate the results of the interventions.